Instagram as a collaborative e-learning tool in higher education - Živojinović, Lazar; Ćurčić, Nevena; Naumović, Tamara (E-business technologies conference proceedings, 2021)
The social network Instagram is used daily by a lot of students. By using Instagram, they share photos and videos, communicate, comment and react to the content of other users. Apart from the current purpose of Instagram, we believe that it can also be used for educational purposes. The aim of this paper is to examine the possibility of using the social network Instagram as a support in the process of collaborative e-learning in higher education. The paper presents the methodological procedure of applying collaborative e-learning activities on Instagram in higher education. Collaborative e-learning activities are organized in the form of challenges and quizzes, with the aim of encouraging creativity and motivation of students to learn, as well as collaboration through mutual interaction in assessing responses to challenges.